How Widespread Are Social Network Effects? Evidence from the Early Twentieth-Century United States - Tan, Hui Ren (Journal of Labor Economics, 2022)
How widespread are social network effects? To answer this, I introduce a page-based approach for identifying individuals living in close proximity and compare how the propensity to work in the same industry varies among worker pairs residing in the same versus different areas. Across the 70 largest cities in the early twentieth-century United States, those from the same area are more likely to work in the same industry. On average, the increase in propensity is around 14%–20% of the baseline mean. These effects also tend to be stronger among single women and migrants from the same country of origin.